Interaction between the phase separation and flow-induced crystallization process in polyethylene/ethylene-methacrylic acid ionomers (surlyn) blends during the film blowing: An in-situ synchrotron radiation X-ray scattering study. (6th May 2022) - Ali, Sarmad; Iqbal, Obaid; Ding, Shenyi; Li, Nian; Guo, Hang
Abstract: A homemade blown film methodology simultaneously coupled with in-situ synchrotron radiation small and wide-angle X-ray scattering (SAXS and WAXS) measurement was assisted to investigate the immiscibility (phase separation) mingled with the flow-induced crystallization of the polyethylene (PE)/surlyn blends during the film blowing process. The whole process is studied within three different regions (I, II, and III) of the bubble along the take-up direction, where the microstructure and temperature evolutions exhibit significantly distinct behaviors. In the SAXS patterns, the equatorial streak signal in the vicinity of the die exit indicates the phase separation among the different polymer components, which is in particular strong in blends consisting of both PE (blends of LDPE, LLDPE, and co-ethylene) and surlyn. The equatorial streak signal attenuates progressively but remains obvious within Region I. The disappearance of phase separation induced by strong flow is an exothermic process, which suppresses the cross-linked crystal network formation prior to the frost line (Af ) within Region II. After the frost line, the main structural evolution is the formation of the non-deformable scaffold during the completion of crystallization along the bubble. It is found that the initial phase separation shows a limited influence on the final structure of the cross-linked crystal network, the effect of phase separation on the crystallization in Region I is eliminated due to the flow field and sufficient crystallization time ultimately. This work should be supportive for extended study and understanding of the structural evolutions of polymer blends during the film blowing. Graphical abstract: Image 1 Highlights: An in-situ synchrotron radiation SAXS/WAXS study on the film blowing process of polymer blends. The effect of phase separation suppresses the cross-linked crystal network formation prior to the frost line. The effect of phase separation on the crystallization is finally eliminated at the end of film blowing.